Analysis of Judd-Ofelt parameters and radioluminescence results of SrNb2O6:Dy3+ phosphors synthesized via molten salt method - (:unkn) unknown (ROYAL SOC CHEMISTRY, 2020)
In this work, Dy3+-doped SrNb(2)O(6)phosphors were fabricated by the molten salt process, which avoids high sintering temperatures, prolonged reaction time and poor compositional homogeneity. All samples crystallized to the orthorhombic columbite structure with space group,P21/c, while a rod-like morphology was observed by scanning electron microscopy (SEM). PL (photoluminescence) and RL (radioluminescence) spectra of SrNb2O6:Dy(3+)exhibited a strong blue emission peak at 576.0 nm related to(4)F(9/2)->(6)H(15/2)transition of Dy. The high RL emission of the(4)F(9/2)-> H-6(15/2)(electric dipole) transition upon X-ray-induced excitation led to a decrease in Dy(3+)local environmental symmetry. The Judd-Ofelt (J-O) theory was applied to the PL excitation spectra for the calculation of optical data such as omega(2),omega(4), and omega(6)parameters, radiative transition probability (A(r)), branching ratios (beta,beta(exp)) and stimulated emission cross-section (sigma(e)). The quantum efficiencies (eta(QE)) varied between 35.47 and 31.93%, which are compatible with theoretical quantum efficiencies based on the Einstein relation. The CIE chromaticity coordinates (x,y) and CCT (correlated color temperature) parameter for 3 mol% phosphor were defined (0.385, 0.432) and 4209 K, respectively.
Keywords: EU3+; PHOTOLUMINESCENCE; ABSORPTION; GLASS; FLUORESCENCE; INTENSITIES; LIFETIME; SPECTRA; IONS; ER3+